Antibacterial effects of new endodontic materials based on calcium silicates - Trišić, Dijana; Ćetenović, Bojana; Zdravković, Nemanja; Marković, Tatjana; Dojčinović, Biljana; Jokanović, Vukoman; Marković, Dejan (Vojnosanitetski pregled, 2021)
Background/Aim. The main task of endodontic treatment is to eliminate pathologically altered tissue, to disinfect root canal space and to obtain its three-dimensional hermetic obturation. The main purpose of this study was to evaluate antimicrobial activity of new endodontic nano-structured highly active calcium silicates based materials albo-mineral plyoxide carbonate aggregate (ALBO-MPCA) and calcium silicates (CS) in comparison to mineral trioxide aggregate (MTA+) and UltraCal XS (CH). Methods. The antimicrobial activity of materials was tested against Staphylococcus aureus (ATCC 25923) and Enterococcus faecalis (ATCC 14506) strains, and following clinical isolates: Rothia dentocariosa, Enterococcus faecalis, Staphylococcus aureus, Streptococcus anginosus and Streptococcus vestibularis using a double layer agar diffusion test. The pH measurements were performed using the pH meter. Total amount of released ions was determined by inductively coupled plasma optical emission spectrometry (ICP-OES). Results. All tested materials showed the best antibacterial potential after 1 h of incubation. After 3h and 24h of the incubation period, the antibacterial potential of all tested materials were similar. The Agar diffusion test showed that ALBO-MPCA, CS and MTA+ had similar inhibition zones (p > 0.05), except in the activity against Staphylococcus aureus where ALBO-MPCA showed better antimicrobial properties than MTA+ in 3h and 24h of the incubation period (p < 0.05). Following 24h of the incubation, the inhibition zones were the strongest with CH against Staphylococcus aureus (16.67 ± 2.34 mm) followed by ALBO-MPCA (14.67 ± 1.21 mm) and the weakest with CS against Enterococcus faecalis (6.50 ± 1.76 mm). CH showed the highest pH, followed by ALBO-MPCA, CS and MTA+. Conclusion. The expressed antibacterial effects indicate that materials based on nano-structured highly active calcium silicates represent effective therapeutic agents for root canal obturation in one-visit apexification treatment, therefore they are recommend for further examination and clinical trials as they are proposed for MTA substitution.